Penile gangrene: an unusual complication of malignant priapism in a patient with renal cell carcinoma - Aynaou, Mohammed (Pan Afr Med J, 2019)
A 68-year-old man presented with priapism and penile gangrene. The patient had no history of penis trauma or medications for erectile dysfunction. Corpus cavernosa aspiration cytology were positive for malignant cells. Total penectomy was performed. Enhanced chest and abdominal computed tomography showed a left renal tumor with pulmonary and hepatic metastases. Ultrasound-guided renal biopsy showed clear cell renal cell carcinoma.